2022
DOI: 10.1186/s12916-022-02447-5
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy and type 1 diabetes in the offspring: a nationwide register-based study with family-based designs

Abstract: Background Maternal smoking during pregnancy was reported to be associated with a reduced risk of type 1 diabetes in the offspring. We investigated whether this association is consistent with a causal interpretation by accounting for familial (shared genetic and environmental) factors using family-based, quasi-experimental designs. Methods We included 2,995,321 children born in Sweden between 1983 and 2014 and followed them for a diagnosis of type … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Although these data suggest a protective effect of maternal smoking on the risk for offspring to develop type 1 diabetes, mechanistic studies are needed to elucidate the underlying pathways behind this link. Despite these findings, we emphasize that smoking during pregnancy should be strongly advised against since it has severe effects on fetal and childhood health [21].…”
Section: The Impact Of Environmental Exposures-metabolic In Utero Env...mentioning
confidence: 75%
See 1 more Smart Citation
“…Although these data suggest a protective effect of maternal smoking on the risk for offspring to develop type 1 diabetes, mechanistic studies are needed to elucidate the underlying pathways behind this link. Despite these findings, we emphasize that smoking during pregnancy should be strongly advised against since it has severe effects on fetal and childhood health [21].…”
Section: The Impact Of Environmental Exposures-metabolic In Utero Env...mentioning
confidence: 75%
“…Also focusing on the influencing factors on metabolic health, a Swedish nationwide register-based study investigated the association between maternal smoking during pregnancy and type 1 diabetes in the offspring [21]. The cohort consisted of nearly three million children born between the years 1983 and 2014, with follow-up until 2020.…”
Section: The Impact Of Environmental Exposures-metabolic In Utero Env...mentioning
confidence: 99%
“…Maternal smoking may also impair pancreatic development or cause epigenetic modifications in offspring [ 62 ]. However, other research has paradoxically shown maternal smoking may reduce type 1 diabetes risk in offspring [ 63 , 64 ]. The mechanisms underlying this discrepancy remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Wei et al [8] provided strong evidence of a lower risk of type 1 diabetes for children exposed to MSDP as compared to unexposed children, by using family-based designs of sibling and cousin comparison analyses. However, this should not preclude the development and implementation of tobacco control policies in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…To control for potential confounders from unmeasured familial background factors, apart from a traditional cohort study design, Wei et al [8] used a family-based, nested case-control study by matching children with type 1 diabetes to their siblings and cousins who were free of diabetes. Sibling and cousin comparisons are quasiexperimental designs, which use design features to help minimise confounding effects from genetic and environmental factors that are shared by family members [9].…”
Section: Maternal Smoking and Risk Of Type 1 Diabetes In The Offspringmentioning
confidence: 99%